基于MF-DFA和SVM的齿轮箱故障诊断 - 刘春林; 潘宏侠; 史斐娜; 蒋红军 (Jixie chuandong)
The fault signal of the gearbox is the complex signal of the non-stationary and nonlinear characteristics,by using the multifractal detrended fluctuation analysis（MF-DFA）and the support vector machine（SVM）to diagnose the fault of the gearbox.The multifractal detrended fluctuation analysis is employed to the extract multifractal singularity index of the gearbox fault,largest singular index,minimum singular index,the width of the singular spectrum,the singular index of extreme value point and so on,and this four fractal parameters are as characteristic parameter.And then the sample of the gearbox different fault state is built,by using the new method of support vector machine,the gearbox fault diagnosis and identification is achieved.Through the study,a new method for mechanical fault diagnosis is provided through the combination of this two methods.There is of great significance for the fault diagnosis and identification of gearbox.